Short-term Outcomes of Pancreatoduodenectomy in Patients with Liver Cirrhosis: A Systematic Review and Meta-analysis - Shahab Hajibandeh, MRCS; Shahin Hajibandeh, FRCS; Alwin Puthiyakunnel Saji; Ayman Ashabi, MRCS; Christopher Brown, FRCS; Nicholas G Mowbray, FRCS; Matthew Mortimer, FRCS; Guy Shingler, FRCS; Amir Kambal, FRCS; Bilal Al-Sarireh, FRCS, PhD (Annals of Surgery Open)
Objectives:. The objective of this study was to compare short-term outcomes of pancreatoduodenectomy between patients with and without liver cirrhosis (LC). Background:. It is not uncommon to encounter a patient with LC and with an indication for pancreatoduodenectomy; however, the knowledge on the outcomes after pancreatoduodenectomy in patients with LC is poorly developed. Methods:. A systematic review and meta-analysis was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement standards. Short-term outcomes of pancreatoduodenectomy between patients with and without LC were compared using random effects modeling and the certainty of the evidence was assessed using the GRADE system. Results:. Analysis of 18,184 patients from 11 studies suggested LC increased the risk of postoperative mortality (odds ratio [OR]: 3.94, P < 0.00001), major complications (OR: 2.25, P = 0.0002), and pancreatic fistula (OR: 1.73, P = 0.03); it resulted in more blood loss (mean difference [MD]: 204.74 ml, P = 0.0003) and longer hospital stay (MD: 2.05 days, P < 0.00001). LC did not affect delayed gastric emptying (OR: 1.33, P = 0.21), postoperative bleeding (OR: 1.28, P = 0.42), and operative time (MD: 3.47 minutes, P = 0.51). Among the patients with LC, Child-Pugh B or C class increased blood loss (MD: 293.33 ml, P < 0.00001), and portal hypertension increased postoperative mortality (OR: 2.41, P = 0.01); the other outcomes were not affected. Conclusions:. Robust evidence with high certainty suggests LC of any severity with or without portal hypertension results in at least a fourfold increase in mortality and a twofold increase in morbidity after pancreatoduodenectomy. Whether such risks increase with the severity of the liver disease or decrease with optimization of underlying liver disease should be the focus of future research.